Is the segmented skill divide perspective useful in migration studies? Evidence from the portuguese case - Marques, José Carlos (2021)
Boundaries among social scientists continuously challenge the scope for obtaining broader reaching views. This constitutes the case for migration studies, generally perceived as interdisciplinary and correspondingly gathering contributions from many social scientists with diverse disciplinary background. For example, many practical and institutional boundaries separate those studying so-called voluntary and forced migration. The same sub-disciplinary division also applies to the study of highly skilled migration. Even when treated as part of overall migration, highly skilled migrants are viewed as so specific that their study must not be mixed in with other migrants. The main aim of this paper involves discussing the relevance of this divide between high and less skilled emigration, trying to understand which aspects place them in the same framework and which facets separate them out into isolated categories. Rather than discussing the issue in general, our purpose is to put forward evidence about sociodemographic profiles, migration strategies, and the integration processes of high and less skilled emigrants moving in the same context in order to systematically compare these groups. The context chosen for such a comparison is Portugal at the beginning of the new millennium: a country that witnessed a strong upsurge in emigration over recent decades in which high skilled and less skilled emigrants both coexisted. The data analysed in this article results from a large-scale survey applied to Portuguese individuals who left the country in the new century.